Thermal performance optimization methods for heat exchangers with accumulation in phase change materials - Neto, Fernando (2023)
The article addresses the need to improve the performance of hot water systems in buildings by proposing a novel technique based upon the use of PCM. A heat exchanger using a PCM was developed and tested. By resorting to numerical models, different assembling processes were tested in order to combine low fin-pipe thermal resistances with high output manufacturing processes. Experimental tests have shown that the system can provide instant hot water for an adequate period of time hence preventing the use of circulating loops with high installation costs and reducing the waste of energy and water.